Upaya Meningkatkan Hasil Belajar Ilmu Pengetahuan Alam dengan Model Discovery Learning Materi Energi dan Perubahannya pada Siswa Kelas VI SDN 1 Sukamenanti, Bandar Lampung - Kusrina, Kusrina (LPPM STKIP PGRI Bandar Lampung, 2021)
The success of the teaching and learning process in the classroom is largely determined by the learning strategy, however complete and clear the other components, without being implemented through the right strategy, these components will have no meaning in the process of achieving goals. Therefore, each teacher will be required to apply certain strategies or methods in the implementation of learning. This research is based on the problems raised from the very low scores of science lessons, namely getting an average grade of 45.3 where only 10.52% scored above the KKM. Therefore, the researcher carried out a follow-up research with the formulation of the problem: How to improve the learning outcomes of Natural Science in the material of Energy and its changes by implementing the Discovery Learning model in Class VI semester II students of SDN 1 Sukamenanti Kedaton District, Bandar Lampung City, 2017-2018 ? While the objectives of this study are: (a) Knowing the improvement of learning outcomes in the Natural Science Matari Energy and its changes after the application of the Discovery Learning model in Class VI semester II students of SDN 1 Sukamenanti, Kedaton District, Bandar Lampung City, 2017-2018 Academic Year. (b) To determine the improvement in the learning achievement of grade VI students at SDN 1 Sukamenanti through the Discovery Learning model. (c) Improving the implementation of Natural Science learning in improving learning outcomes in class VI semester II students of SDN 1 Sukamenanti, Kedaton District, Bandar Lampung City, 2017-2018 Academic Year This research uses action research as many as three rounds. Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The target of this research is the sixth grade students of SDN 01 Sukamenanti, Kedaton District, Bandar Lampung City, 2016-2017 Academic Year. The data obtained are in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning outcomes increased from cycle I to cycle III, namely, cycle I (26.31%), cycle II (47.36%), cycle III (89.47%). The conclusion of this study is that the Discovery Learning model can have a positive effect on the learning outcomes of Grade VI students of SDN 1 Sukamenanti, Kedaton District, Bandar Lampung City for the 2016-2017 Academic Year, and this learning model can be used as an alternative to learning science.